GAMMA IRRADIATION PRESERVATION OF CHESTNUT FRUITS: EFFECTS ON COLOR AND TEXTURE - Amilcar L. Antonio; Angela Fernandes; Albino Bento; Armando Ferreira; M. Joao Trigo; M. Luisa Botelho; Begona Quintana; Elsa Ramalhosa (European Scientific Journal, ESJ, 2014)
Chestnuts are a seasonal fruit that must be postharvest treated to meet food safety regulations. In this study the effect of gamma irradiation on color and texture of chestnut fruits from a European variety (Castanea sativa Miller) was reported. The fruits were subjected to gamma irradiation doses of 0.5, 3 and 6 kGy, with color and texture properties analyzed along a typical commercial period for this fruit after postharvest treatment, at 0, 15 and 30 days of storage. For L and b color parameters, significant differences (p < 0.05) were observed with irradiation dose (ID) only for higher doses of 3 kGy and 6 kGy. Along storage time (ST) significant differences (p < 0.05) were observed for fruits interior (half-cutted) after 15 days of storage. Regarding texture, differences on fruits were only detected for chestnuts irradiated with 6 kGy. With this study we can identify the maximum acceptable dose for irradiation processing of these fruits, concluding that gamma irradiation could be a promising alternative technology for postharvest disinfestation of European chestnuts varieties, to meet food safety international trade regulations, not affecting significantly two important parameters for the consumer, the color and texture.